Pengaruh Pengetahuan Perpajakan, Self Efficacy, Motivasi, dan Efektivitas Pembelajaran terhadap Minat Mahasiswa Akuntansi dalam Berkarir di Bidang Perpajakan : (Studi pada Mahasiswa Akuntansi di Universitas Kahuripan Kediri) - Dewi Mardian; Eko Prasetyo (Asosiasi Riset Ekonomi dan Akuntansi Indonesia, 2024)
This research aims to examine the influence of the variables tax knowledge, self-efficacy, motivation, and learning effectiveness on accounting students' interest in pursuing a career in the field of taxation. This research uses quantitative methods with data sources from primary data in the form of distributing questionnaires which have been answered by all respondents and the results will be analyzed with the help of the Statistical Package of Social Science (SPSS) version 29 as a test tool. The population in this study were accounting students at Kahuripan Kediri University Class of 2020-2022. The sample used in this research was 65 students using the purposive sampling method and the Slovin formula. The data analysis method used in this research is multiple linear regression analysis. The results of the research show that the independent variables tax knowledge, self-efficacy, and learning effectiveness have a significant effect on the dependent variable, namely accounting students' interest in pursuing a career in taxation, while the independent variable motivation has no significant effect on the dependent variable, namely accounting students' interest in pursuing a career in taxation.